2014
DOI: 10.3389/fmicb.2014.00708
|View full text |Cite
|
Sign up to set email alerts
|

Chaophilic or chaotolerant fungi: a new category of extremophiles?

Abstract: It is well known that few halophilic bacteria and archaea as well as certain fungi can grow at the highest concentrations of NaCl. However, data about possible life at extremely high concentrations of various others kosmotropic (stabilizing; like NaCl, KCl, and MgSO4) and chaotropic (destabilizing) salts (NaBr, MgCl2, and CaCl2) are scarce for prokaryotes and almost absent for the eukaryotic domain including fungi. Fungi from diverse (extreme) environments were tested for their ability to grow at the highest c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 57 publications
2
48
0
Order By: Relevance
“…muriae can grow at MgCl 2 concentrations of up to 11%-17%, while W . ichthyophaga can grow even up to 20% MgCl 2 [23, 24, 72]. Addition of the chaotropic MgCl 2 as solute to the growth media resulted either in very small production of secondary metabolites or even their complete absence.…”
Section: Resultsmentioning
confidence: 99%
“…muriae can grow at MgCl 2 concentrations of up to 11%-17%, while W . ichthyophaga can grow even up to 20% MgCl 2 [23, 24, 72]. Addition of the chaotropic MgCl 2 as solute to the growth media resulted either in very small production of secondary metabolites or even their complete absence.…”
Section: Resultsmentioning
confidence: 99%
“…Extensive studies have identified fungi that thrive on media with NaCl. In contrast, few strains are able to growth in the presence of MgCl 2 [19].…”
Section: Wallemia Mellicolamentioning
confidence: 99%
“…4). According to Zajc et al [19], the type of salt added to media affects the growth of strains. Extensive studies have identified fungi that thrive on media with NaCl.…”
Section: Wallemia Mellicolamentioning
confidence: 99%
“…Alternatively, halotolerance refers to growth capacity in highly saline environments, and osmotolerance refers to resistance to osmotic pressure, that is, salts or sugars (Pitt, 1975;Pitt & Hocking, 1997). It is noteworthy that certain solutes, termed chaotropic, are more inhibitory than other kosmotropic solutes, because they destabilize macromolecules (Lievens et al, 2014;Zajc et al, 2014).…”
Section: Resistance To the Physicochemical Properties Of Food Water Amentioning
confidence: 99%
“…One common solute, glycerol, is produced by the well-studied high osmolarity glycerol (HOG) pathway. The HOG pathways are initiated in response to NaCl changes, producing or expelling glycerol as needed to survive osmotic stress (Gostinčar et al, 2014;Plemenitaš et al, 2014;Zajc et al, 2014).…”
Section: Resistance To the Physicochemical Properties Of Food Water Amentioning
confidence: 99%